Mathematical Science Reformulate Convex Relaxation in Logic Based Optimization - Kishore, Rajeev (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: medium none; padding-left: 0in; padding-bottom: 1pt; border-left: medium none; padding-top: 0in; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> Abstract We present a convex conic Relaxation for a problem of maximizing an indefinite quadratic form over a set of, convex constraints on the squared variables, convex envelopes of non convex functions are widely used to calculate lower bounds of solutions of non linear programming problem (NLP). This paper proposes a non linear continuous convex envelope for (Linear, bilinear, trilinear fractional) monomial terms of odd degree and the range of variables (x, y, z) includes zero. We also drive a linear relaxation from the proposed envelope and computer both the Linear and non linear formulations with relaxations obtained using other approaches. Â <div style="border-right: medium none; padding-right: 0in; border-top: medium none; padding-left: 0in; padding-bottom: 1pt; border-left: medium none; padding-top: 0in; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> Keywords: Odd degree, Monomial, Convex relaxation, Global optimization Department of Mathematic, Jamuna Prasad Memorial Degree College, Bareilly Please Cite This Article As: Rajeev Kishore. 2010. Mathematical Science Reformulate Convex Relaxation in Logic Based Optimization. J. Exp. Sci. 1(5):25-27. Â